ANALISIS MUTASI G1896A VIRUS HEPATITIS B PADA PASIEN DENGAN HEPATITIS B KRONIS DAN PENYAKIT HATI TAHAP LANJUT DI RSUP DR. SARDJITO YOGYAKARTA - , JULIAN RAYMOND IRWEN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Hepatitis B infection is one of the most common infection in the world which has a very high morbidity and mortality. Indonesia is among the countries in the world where the amount of people with hepatitis B infection is very high. Chronic hepatitis B infection may progress into advanced liver disease, and one of the factor that may trigger the infection progressing into advanced liver disease is the virus mutation. There are a lot of mutation in hepatitis B virus, and one of them is the G1896A mutation in precore region. Several studies that has been conducted in other countries suggest this mutation is one of the factor that will increase the risk of hepatitis B chronic infection in becoming advanced liver disease. However, the study on G1896A mutation in RSUP Dr. Sardjito Yogyakarta has not been conducted. Objective: To investigate the difference of prevalence of G1896A mutation between patient with chronic hepatitis B infection and advanced liver disease. Methods: Observational cross-sectional study, involving 80 patients that were divided into 2 groups. The first group consist of patients with either liver cirrhosis or hepatocellular carcinoma which were grouped as advanced liver disease (n=40, 31 male and 9 female, mean age 54.38Â±11.58 years old), and the second group consist of patients with chronic hepatitis B infection (n=40, 27 male and 13 female, mean age 36.63Â±12,76 years old). The analysis was being done during period of September through December 2013. The chronic hepatitis B infection is patient who have the positive in HBsAg test, but did not fulfill any diagnosis criteria of either liver cirrhosis or hepatocellular carcinoma. The mutation then analyzed with direct sequencing method. Results: The presence of G1896A mutation were observed in 16(40%) patients with advanced liver disease and 11(27.5%) patients with chronic hepatitis B infection. The difference of G1896A mutation prevalence between the two groups is not statistically significant. Conclusion: There is no significant difference in the presence of G1896A mutation between patient with advanced liver disease and patient with chronic hepatitis B infection. However, there is a trend that the prevalence of G1896A mutation among the patient with advanced liver disease is a little bit higher, which may suggest that G1896A mutation may have a role in triggering the change of course from chronic hepatitis B infection into advanced liver disease.